Medición de la capacidad de emprendimiento dinámico del clúster agroindustrial de quinua en el departamento del Cauca (2019)
For this project, the dynamic entrepreneurship capacity of a quinoa agroindustrial cluster in the department of Cauca will be evaluated, taking as a starting point the advances and findings made by governmental and state entities, the methodology that will be used is an adaptation carried out by the Colombian firm Red Clúster Colombia, since it accommodates the natural conditions of the Colombian territory, and collects the necessary pillars to give a quantitative and qualitative measurement of the economic reality that the department of Cauca is facing in front of a new product and with great growth potential, but which can be affected by the conditions of social and cultural problems and problems of land restitution by the state